PELATIHAN PENGEMBANGAN MULTIMEDIA BERBASISKAN KONTEKSTUAL UNTUK PEMBELAJARAN INQUIRY BAGI GURU-GURU SMPN 19 DAN SMPN 34 KABUPATEN SOLOK SELATAN - Hufri Hufri (Fakultas MIPA Universitas Negeri Padang, 2018)
In the education sector of South Solok distric, it is still lagging behind other regions, this can be seen from the results of the 2016 UN ranking which is ranked 16th out of 19 cities /distric in West Sumatra. Based on observations and discussions conducted on several teachers and principals, this is due to the learning that students are more likely to wait for what is conveyed by the teacher or the learning is still teacher-centered. Then in learning the teacher has not used a variety of learning media. The media used cannot accommodate the facts of students' daily conditions, although in reality there are many types and various facts around students that can be developed and utilized to support learning. This devotion activity aims to improve the competence of teachers of South Solok Regency Junior High School through contextual based multimedia development training for inquiry learning. To achieve these objectives, the method used consists of several steps, namely the steps of orientation, preparation, implementation, monitoring and evaluation as well as the steps of data analysis and report preparation. The instrument used was a test of understanding of the material and questionnaire on participant's response. Data analysis techniques used are paired t test and percentage analysis. The results of the analysis of pretest and posttest data and questionnaire responses of training participants, obtained the average pretest value was 41.36 for the average posttest score was 57.27. So the average value, posttest is higher than the pretest value. Based on the results of the t test obtained a significance value of 0.000 <0.05, thus it can be concluded that there is a difference between the results of the pretest and posttest. Where the posttest results are better than the results of the pretest, this shows that there is an increase in the ability of teachers to develop contextual-based multimedia for inquiry learning. Based on the questionnaire given at the end of the training activity, the results showed that the participants stated that this activity was very useful and related to the subjects taught at school